Movement pattern of throwing drag-flick of the U-21 field hockey - Antonio, R.; López De Subijana, C.; Navarro, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In field hockey, the drag-flick is one of the most effective throwing in penalty corner (McLaughlin, 2007; Pineiro, 2008). The objectives of this study were to describe the sequence of linear velocities of the kinematic chain during the drag-flick and to determine the throwing patterns of sample players. Methods: The sample were three men (19,8 ± 0,9 years-old; 69,9 ± 7,2 Kg.; 177,4 ± 6,8 cm and 5 ± 1 years of experience in the skill) and a woman (18,8 years-old; 71,6 Kg.; 171,3 cm and 6 years of experience in the skill) participated in this study. They were all drag-flickers and members of the under-21 Spanish national team. Each player executed 20 drag-flicks. Six automatic capture Vicon cameras sampling at 250 Hz were used to capture the positions of the reflective markers. For the normality of the distribution a Kolmogorov-Smirnov test was made. Not all variables meet the criteria of normality and a Kruskal-Wallis and Mann-Whitney test were done to determine and to quantify the differences between variables (a = 0,05). Later the Bonferroni´s correction was applied which placed the significant level at a/6 = 0,00833. Results and Discussion: The results confirmed the existence of a proximal-distal sequence of movements of the kinematics chain of the body segments (Bretigny, Seifert, Leroy & Chollet, 2008; Lopez de Subijana , Juarez, Mallo & Navarro, 2010). The relative timing (TRel) of movement was determined by the instants when the maximal speeds were reached. They provided relevant information about the coordination of this skill. Based on the TRel it has been described different patterns of drag-flick. Conclusions: It has been established ranges of time to describe the most effective pattern for these throwers. Acknowledge This study was funded by the Spanish Sport Council (Ref n= P08-1110-338)